Liver Disease: A Retrospective Hospital Based Study in Addis Ababa-Ethiopia - Samson, Erkabu; Bisrat, Demeke; Hailu, Desallegn; Selam, Getachew (Journal of Spleen And Liver Research, 2021)
Background Liver disease has caused significant morbidity and mortality worldwide. Its epidemiologic and clinical pattern, however, is not well characterized in sub-Saharan countries. Objective This study aimed to describe demographic, clinical characteristics, and patterns of liver disease in a community hospital in Addis Ababa, Ethiopia. Method A retrospective hospital-based study was conducted on patients with liver disease admitted at Ras Desta Damtew memorial hospital, in Addis Ababa-Ethiopia, from February 2015 to April 2020. Result Of the total 212 patients majority, 78.8% were male, 49.1% of patients were in the age range of 31-50 with a median age of 42. The most common initial clinical presentation was ascites (87.7 %), and more than half of patients (56.6%) had a history of alcohol misuse documented on their medical charts. Chronic liver disease (cirrhosis) was found in 177 (83.5%), and Hepatocellular Cancer accounted for 7.5% of the patients. Alcohol misuse caused 45% of chronic Liver Disease, followed by Hepatitis B virus infection. Conclusion Chronic liver disease is the most common form of liver disease, and the most affected were middle-aged men. The common cause of chronic liver disease was alcohol followed by hepatitis B virus infection.
Keywords: Liver disease; Alcohol misuse; Ras Desta Damtew Memorial Hospital; Addis Ababa